The Effect of the 2024 Presidential Election on IDX80 Index Share Price on the Indonesian Stock Exchange - Dwiningsih, Sri; Ananda, Anton Ferry; Qawi, Fazil (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The aim of the author in conducting this research is to determine the Impact Analysis of the 2024 Presidential Election on Share Prices on the IDX80 Index on the Indonesian Stock Exchange. The method used by the author in conducting this research is the event study method and the Wilcoxon-paired signed rank test. Data processing was carried out using IBM SPSS STATISIC 25. The population of this study was all companies included in the IDX80 index in 2024 on the Indonesia Stock Exchange with the number of samples taken according to the researchers' criteria of 31 IDX80 index companies. Research results There is a significant average difference between stock prices pre and post voting for the 2024 Presidential Election on the IDX80 index listed on the Indonesian Stock Exchange. The Indonesian capital market is included in the semi-strong form of information efficient market, as a representation of the market response to the Presidential Election event. 2024. This event contains information and causes a market reaction. Market reactions can be seen from market returns. The discovery of returns around the 2024 presidential election means that the market is efficient because stock prices quickly and fully reflect all available information.